2014
DOI: 10.1123/tsp.2013-0141
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Athlete Leaders on Team Members’ Team Outcome Confidence: A Test of Mediation by Team Identification and Collective Efficacy

Abstract: Research on the effect of athlete leadership on pre-cursors of team performance such as team confidence is sparse. To explore the underlying mechanisms of how athlete leaders impact their team's confidence, an online survey was completed by 2,867 players and coaches from nine different team sports in Flanders (Belgium). We distinguished between two types of team confidence: collective efficacy, assessed by the CEQS subscales of Effort, Persistence, Preparation, and Unity; and team outcome confidence, measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
86
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(101 citation statements)
references
References 33 publications
11
86
1
3
Order By: Relevance
“…Relatedly, experimental research has shown that, because it enhances team members' social identification, the confidence leaders express in a team is a powerful determinant of basketball players' success in competition [90](see also [157]). …”
Section: Social Identity Is the Basis For Sports Group Leadershipmentioning
confidence: 99%
“…Relatedly, experimental research has shown that, because it enhances team members' social identification, the confidence leaders express in a team is a powerful determinant of basketball players' success in competition [90](see also [157]). …”
Section: Social Identity Is the Basis For Sports Group Leadershipmentioning
confidence: 99%
“…team outcome confidence), which is more susceptible to external factors such as the opponent, dubious referee decisions or a lucky goal. Given its stronger link with the subsequent team performance, coaches and athlete leaders should primarily focus on enhancing players' collective efficacy, which in turn may foster the team's outcome confidence (Fransen, Coffee, Vanbeselaere, Slater, De Cuyper, & Boen, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…First, although the team's performance was demonstrated to be a significant predictor of players' team confidence, it should be noted that the production of team confidence is an interpersonal process, brought about not only by perceptions of previous performances, but also by persuasive actions of the coach or athlete leaders, by motivational and tactical communication within the team and by the enthusiasm expressed by the team members (Fransen, Coffee, et al, 2014;Fransen et al, 2012;Ronglan, 2007). Future research may investigate how these behaviours affect players' team confidence within a game and as such the subsequent team performance.…”
mentioning
confidence: 97%
“…Extant research indicates that it is strongly linked to issues at both ends of the performance spectrum; to sudden declines in performance efficacy [6] and also to the development of strong coping strategies in athletes [2,7]. Consequently, the "sources" of confidence (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Confidence is one of the major contemporary concerns in the psychology of sporting performance [1][2][3][4][5]. Extant research indicates that it is strongly linked to issues at both ends of the performance spectrum; to sudden declines in performance efficacy [6] and also to the development of strong coping strategies in athletes [2,7].…”
Section: Introductionmentioning
confidence: 99%